Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP Berdasarkan Gender - Refli Annisa; Yenita Roza; Maimunah Maimunah (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this study was to analyze the mathematical problem solving abilities of junior high school students based on the gender of the students. This research is a qualitative descriptive study. The subjects in this study were 24 students of class VIII SMPN 3 Bangkinang consisting of 12 male students and 12 female students. Then 6 subjects were selected, namely 3 men and 3 women who had high, medium, and low category mathematical problem solving abilities. The results of the answers would be described in answering the questions. The research was conducted in the even semester of the 2020/2021 school year. The analysis was carried out by giving a written test in the form of description questions, amounting to 3 questions. The material being tested is the material cubes and blocks. The results showed that the mathematical problem solving abilities of female students were superior to male students.